2017
DOI: 10.1002/crat.201700067
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Selenide‐Based Heterostructure From a Designed Precursor†

Abstract: The formation of the ferecrystalline compound (SnSe) 1.15 VSe 2 is studied utilizing complementary X-ray diffraction techniques, differential scanning calorimetry, compositional analysis, scanning transmission electron microscopy, and X-ray absorption spectroscopy. A careful analysis unravels the formation mechanism, where a simultaneous crystallization of the individual constituents goes hand in hand with the formation of the superlattice structure. SnSe 2 monolayers form along with SnSe and VSe 2 units in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…The first MLC from the Pb–V–Se phase diagram was not found until 2020 by Reisinger and Richter in Vienna 26,27 by annealing of weighted binary alloys with a mineralising agent of NH 4 Cl for several months. On the other hand, VSe 2 has been succesfully combined with SnSe, 28–30 SnSe 2 , 31 BiSe, 32 LaSe 1− x , 33 EuSe 33 and PbSe 34–36 in ferecrystals. Cordova et al 37 even demonstrated that [(PbSe) 1+ δ ] m (VSe 2 ) 1 ferecrystals with an odd number of PbSe monolayers in the unit cell can be prepared with MER, if the number of monolayers per repeat unit is ≥7 (which would correspond to m = 3.5 bilayers in the above definition).…”
Section: Introductionmentioning
confidence: 99%
“…The first MLC from the Pb–V–Se phase diagram was not found until 2020 by Reisinger and Richter in Vienna 26,27 by annealing of weighted binary alloys with a mineralising agent of NH 4 Cl for several months. On the other hand, VSe 2 has been succesfully combined with SnSe, 28–30 SnSe 2 , 31 BiSe, 32 LaSe 1− x , 33 EuSe 33 and PbSe 34–36 in ferecrystals. Cordova et al 37 even demonstrated that [(PbSe) 1+ δ ] m (VSe 2 ) 1 ferecrystals with an odd number of PbSe monolayers in the unit cell can be prepared with MER, if the number of monolayers per repeat unit is ≥7 (which would correspond to m = 3.5 bilayers in the above definition).…”
Section: Introductionmentioning
confidence: 99%
“…49 The importance of local composition is also seen in a paper by Falmbigl and coworkers, which involved the reaction of a Sn|Se|V|Se precursor with a nanoarchitecture similar to that of precursors I and A but with an intermediate amount of Se. 60 In this precursor, annealing at 100 °C resulted in the simultaneous crystallization of SnSe 2 , SnSe, and VSe 2 and all of these exhibited significant in-plane grain growth between 100 °C and 300 °C. The simultaneous formation of all three constituents suggests that the difference between the nucleation barriers for the three phases is small and controlled by the local Sn and Se composition.…”
Section: ■ Discussionmentioning
confidence: 93%
“…There are large activation barriers between the different products initially formed because it would be necessary to create regions with the local composition required to nucleate the different alternatives, and this would require long-range solid-state diffusion which has a high activation energy . The importance of local composition is also seen in a paper by Falmbigl and co-workers, which involved the reaction of a Sn|Se|V|Se precursor with a nanoarchitecture similar to that of precursors I and A but with an intermediate amount of Se . In this precursor, annealing at 100 °C resulted in the simultaneous crystallization of SnSe 2 , SnSe, and VSe 2 and all of these exhibited significant in-plane grain growth between 100 °C and 300 °C.…”
Section: Discussionmentioning
confidence: 97%